Design of municipal wastewater treatment plants (McGraw-Hill, 2010)
This three-volume set from the Water Environment Federation and the Environmental and Water Resources Institute of the American Society of Civil Engineers presents the current plant planning, configuration, and design practices of wastewater engineering professionals, augmented by performance information from operating facilities. Design of Municipal Wastewater Treatment Plants, Fifth Edition, includes design approaches that reflect the experience of more than 300 authors and reviewers from around the world